2013
DOI: 10.1371/journal.pone.0073073
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Preventive Therapy with Sulfadoxine-Pyrimethamine for Malaria in Pregnancy: A Cross-Sectional Study from Tororo, Uganda

Abstract: BackgroundIntermittent preventive treatment during pregnancy (IPTp) with sulfadoxine-pyrimethamine (SP) is widely recommended in sub-Saharan Africa to reduce the risk of malaria and improve birth outcomes. However, there are reports that the efficacy of IPTp with SP is waning, especially in parts of Africa where antimalarial resistance to this drug has become widespread.Methodology/Principal FindingsWe conducted a cross-sectional study of 565 HIV-uninfected women giving birth at Tororo District Hospital in sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 29 publications
2
35
2
Order By: Relevance
“…This corroborates with other works that reported that 2 or more doses of SP were not significantly associated with LBW. 24 Breech presentation has not been established in earlier literature as a risk factor for low birth weight among adolescents just as what this study suggests. The observed association between breech presentation and low birth weight in all the mothers in the study (p=0.046) needs to be interpreted with some caution as the presence of an association does not mean causation.…”
Section: Discussioncontrasting
confidence: 47%
“…This corroborates with other works that reported that 2 or more doses of SP were not significantly associated with LBW. 24 Breech presentation has not been established in earlier literature as a risk factor for low birth weight among adolescents just as what this study suggests. The observed association between breech presentation and low birth weight in all the mothers in the study (p=0.046) needs to be interpreted with some caution as the presence of an association does not mean causation.…”
Section: Discussioncontrasting
confidence: 47%
“…On the other hand, spin-column extraction using protocols from Qiagen, which involves lysis with proteinase K instead of saponin, may have an advantage in obtaining DNA from older samples, which are difficult to lyse, especially when parasite densities are high such that inefficiencies of the column are relatively unimportant. Anecdotally, we have also found that spin-column extraction appears to work better than the saponin/Chelex method for DBS samples obtained from placentas, 15 perhaps for the same reason. A positive finding in our study is that saponin/Chelex extracted DNA was remarkably stable during long-term storage at −20 C, and that the detectability of parasite DNA was not affected by repeated freeze thaws.…”
Section: Discussionmentioning
confidence: 84%
“…The studies were conducted between 2009 and 2013 at 8 sites in 6 countries: 2 countries in West Africa (Mali [2 sites] and Burkina Faso [16]) and 4 in eastern and southern Africa (Zambia [19, 20], Malawi [2 sites] [15, 17, 21], Uganda [14], and Kenya [18]).…”
Section: Methodsmentioning
confidence: 99%
“…We conducted multicountry studies [1419] in sub-Saharan Africa to investigate 2 effects of IPTp-SP: (1) its efficacy at clearing existing peripheral infections in asymptomatic pregnant women receiving their first dose of IPTp-SP; and (2) the effectiveness of IPTp-SP at increasing mean birth weight, reducing LBW, or improving other birth outcomes. Here we present individual-level pooled analyses of peripheral parasite clearance and birth outcomes to better quantify the impact of SP resistance on IPTp-SP effectiveness.…”
mentioning
confidence: 99%